Implementation of Wound Care with Simple Island Dressing Technique in Inguinal Hernia Lateralis Postoperative Patients - Fitriani, Ade; Istiqamah, Syffa Yunia; Lismayanti, Lilis (LPPM STIKes Muhammadiyah Ciamis, 2025)
A Lateral inguinal hernia is a protrusion of the contents of the abdominal cavity that comes out of the peritoneal cavity through the weak part of the abdominal wall which contains the intestines, intestinal suspension or other abdominal organs. According to the category of causes of disease in Indonesia in 2020, hernia was ranked eighth. Lateral inguinal hernias result from weakening of the abdominal wall and are caused by increased intra-abdominal pressure. Lateral inguinal hernia requires immediate surgical treatment to prevent dangerous complications. This surgical procedure is called a herniotomy. After post-operative herniotomy, to avoid infection, post-operative wound care is required, namely by treating the wound with a simple island dressing technique. This case study aims to determine the results of implementation of wound care using the simple island dressing technique. This research uses a descriptive method of case study design with a nursing care approach, including assessment, diagnosis planning, implementation and evaluation. Data collection through interviews, observation, physical examination and documentation studies. The results of a case study after being given wound care using the simple island dressing technique to a post-operative patient, Mr. R the condition of the wound improved, there were no signs of infection or complications. Conclusion of post-operative care performed on post-operative patients with lateral inguinal hernia. The author planned and implemented the simple island dressing technique so that the wound improved and no signs of infection appeared.